2011
DOI: 10.4049/jimmunol.1003757
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus Infection in the Brain and Lung Leads to Differential Type I IFN Signaling during Acute Infection

Abstract: Using an accelerated and consistent SIV pigtailed macaque model of HIV-associated neurologic disorders, we have demonstrated that virus enters the brain during acute infection. However, neurologic symptoms do not manifest until late stages of infection, suggesting that immunological mechanisms exist within the CNS that control viral replication and associated inflammation. We have shown that IFN-β, a type I IFN central to viral innate immunity, is a major cytokine present in the brain during acute infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 77 publications
0
32
1
Order By: Relevance
“…For example, macrophages and microglia are thought to be the major producers of IDO1 in the brain (41), whereas mDCs may express the highest level of IDO1 in the spleen (data shown here) and lymph nodes (2) during HIV/SIV infection. Conversely, IFNα subtypes are known to differ in different tissue sites; such differences could modulate the induction of IDO1 or IDO1 modulators (63). Future studies will be necessary in order to examine the cell-specific requirements of IDO and other KP enzyme induction in other peripheral tissue sites and during acute vs. chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophages and microglia are thought to be the major producers of IDO1 in the brain (41), whereas mDCs may express the highest level of IDO1 in the spleen (data shown here) and lymph nodes (2) during HIV/SIV infection. Conversely, IFNα subtypes are known to differ in different tissue sites; such differences could modulate the induction of IDO1 or IDO1 modulators (63). Future studies will be necessary in order to examine the cell-specific requirements of IDO and other KP enzyme induction in other peripheral tissue sites and during acute vs. chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Antiretroviral drug penetration into tissues that may be reservoirs of HIV infection, such as the central nervous system, gastrointestinal tract and lymph nodes, is variable [39,40]. Conversely, IFN-alpha has shown good penetration into the liver, kidney, gastrointestinal tract, pancreas, spleen, and lung in models involving mice [41], and into the central nervous system in SIV-infected pigtailed macaque models [42]. IFN-alpha can also eradicate HCV from the liver even when chronic infection has been established, indicating its excellent penetration into this tissue [11].…”
Section: Potential Role Of Ifn-alpha In Hiv Reservoirsmentioning
confidence: 99%
“…Our group has made the novel discovery that type I IFN signaling in the central nervous system (CNS) in response to SIV infection occurs in a more complex, noncanonical manner (2). Using an accelerated, consistent pigtailed macaque SIV model of HIV associated neurological disease, we have shown that while IFNβ is induced during acute SIV infection in brain, IFNα is simultaneously down regulated and associated with a suppression of signaling modulators downstream of the IFN receptor, including Tyk2, STAT1 and IRF7.…”
Section: Introductionmentioning
confidence: 99%